Li‐Ion Cooperative Migration and Oxy‐Sulfide Synergistic Effect in Li14P2Ge2S16−6xOx Solid‐State‐Electrolyte Enables Extraordinary Conductivity and High Stability. Issue 11 (20th February 2020) - Zhang, Bingkai; Weng, Mouyi; Lin, Zhan; Feng, Yancong; Yang, Luyi; Wang, Lin‐Wang; Pan, Feng
Abstract: Critical to the development of all‐solid‐state lithium‐ion batteries technology are novel solid‐state electrolytes with high ionic conductivity and robust stability under inorganic solid‐electrolyte operating conditions. Herein, by using density functional theory and molecular dynamics, a mixed oxygen‐sulfur‐based Li‐superionic conductor is screened out from the local chemical structure of β‐Li3 PS4 to discover novel Li14 P2 Ge2 S8 O8 (LPGSO) with high ionic conductivity and high stability under thermal, moist, and electrochemical conditions, which causes oxygenation at specific sites to improve the stability and selective sulfuration to provide an O‐S mixed path by Li‐S/O structure units with coordination number between 3 and 4 for fast Li‐cooperative conduction. Furthermore, LPGSO exhibits a quasi‐isotropic 3D Li‐ion cooperative diffusion with a lesser migration barrier (≈0.19 eV) compared to its sulfide‐analog Li14 P2 Ge2 S16 . The theoretical ionic conductivity of this conductor at room temperature is as high as ≈30.0 mS cm −1, which is among the best in current solid‐state electrolytes. Such an oxy‐sulfide synergistic effect and Li‐ion cooperative migration mechanism would enable the engineering of next‐generation electrolyte materials with desirable safety and high ionic conductivity, for possible application in the near future. Abstract : A new oxygen‐sulfide Li14 P2 Ge2 S8 O8 (LPGSO) material decorated with PO4 and GeS4 structural units is designed for all‐solid‐state lithium batteries. The oxygen‐sulfide LPGSO crystal not only has high stability but also has high room temperature ion conductivity. This concept of mixing structural units opens up a broader scope for next generation materials toward desirable high stability and high conductivity.